Uji Aktivitas Antidiabetes Fraksi Etil Asetat Daun Seledri (Apium graveolens L.) Terhadap Tikus Jantan Wistar (Rattus norvegicus) - Rena Meutia; Novitaria br Sembiring; Octavian Ashido Nababan; Nerly Simanjuntak; Erida Novriani; Nurasni Nurasni (Journal of Pharmaceutical and Sciences, 2023)
The high population of diabetic patients every year is increasing, with the number of diabetic patients increasing by 463,000 in 2019. Estimates of Idiabetic foot in 2045 the number of the diabetic patient will be 700.000.000 patients. Celery leaves are used as an anti-diabetic (Apium graveolens L.). This study aimed to determine the anti-diabetic activity of the ethyl acetate fraction in celery leaves against male Wistar rats. Celery leaf Simplicia powder was extracted with 70% ethanol solvent in the maceration method. After obtaining 70% ethanol extract, then fractionation of n-hexane, ethanol-water, and ethyl acetate was carried out. The anti-diabetic test of the ethyl acetate fraction on celery leaves used the compound alloxan at a dose of 150 mg/kg BW. This study obtained the results of the ethyl acetate fraction in celery leaves at a dose of 300 mg/kg, which had the highest anti-diabetic activity with a reduction percentage of 65% compared to the positive control with a reduction percentage of 64%. The contents of chemical compounds from the ethyl acetate fraction in celery leaves are alkaloids, flavonoids and saponins.